2018
DOI: 10.1108/jd-05-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Distribution features and intellectual structures of digital humanities

Abstract: Purpose The purpose of this paper is to conduct a retrospective bibliometric analysis of documents about digital humanities, an emerging but interdisciplinary movement. It examines the distribution of research outputs and languages, identifies the active journals and institutions, dissects the network of categories and cited references, and interprets the hot research topics. Design/methodology/approach The source data are derived from the Web of Science (WoS) core collection. To reveal the holistic landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 66 publications
5
53
0
Order By: Relevance
“…The data source plays an important role in conducting a bibliometric study. In this study, the literature data were collected from the WoS core collection, which includes about 18,000 high-quality journals and 1.3 billion cited references beginning in 1900 (Wang 2018). The literature retrieval strategy was based on advanced search, and the specific strategies are given below.…”
Section: Data Source and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The data source plays an important role in conducting a bibliometric study. In this study, the literature data were collected from the WoS core collection, which includes about 18,000 high-quality journals and 1.3 billion cited references beginning in 1900 (Wang 2018). The literature retrieval strategy was based on advanced search, and the specific strategies are given below.…”
Section: Data Source and Methodologymentioning
confidence: 99%
“…Therefore, Price's Law is presented, and it has been widely employed to identify core authors in a certain field (e.g. Wang 2018;Zhong 2012). In this study, Price's Law is employed to calculate the minimum number of publications published by one scholar, and the equation of the threshold number of publications is as follows:…”
Section: Influence Of Authorsmentioning
confidence: 99%
“…In this phase we will refer to the results of the bibliometric studies of Tang et al, (2017) and Wang (2018) in order to assess possible correlations in terms of themes and standards seen in our study with respect to the analysis of international productivity within DH.…”
Section: Phase 4: Analysis and Discussionmentioning
confidence: 99%
“…Sula (2013) demonstrates the growing interest in DH within LIS publications, as well as a major overlap of interests, competences and institutional structures between the two disciplines. Wang (2018), meanwhile, describes digital humanities as an interdisciplinary movement and the result of a dynamic dialogue between humanistic exploration and digital means. Authors such as Dalbello (2011), Koltay (2016), Poole (2017) o Robinson et al, (2015) reinforce this idea of common interests, suggesting that DH and LIS complement one another to a very great degree since both disciplines focus on documents and recorded information.…”
Section: Digital Humanities and Library And Information Sciencementioning
confidence: 99%
“…This collaboration is reflected in the interaction between different disciplines on the one hand, and the cooperation between institutions and agencies on the other. Existing studies have explored interdisciplinary collaboration in DH mainly from the perspective of academic literature using bibliometric methods (Su, 2020; Tang et al, 2017; Wang, 2017), while fewer studies have revealed the interdisciplinary characteristics of DH from the perspective of public‐funded projects. We believe that compared to academic literature, the analysis of DH projects at the macro level can provide a clearer picture of interdisciplinary collaborations and thus better reveal the collaborative relationships between disciplines and institutions as well as the characteristics of digital scholarship.…”
Section: Introductionmentioning
confidence: 99%